PERCEPTIONS OF SMAS PAB 8 SAENTIS STUDENTS REGARDING THE INDEPENDENT LEARNING CURRICULUM IN PHYSICAL EDUCATION, SPORTS AND HEALTH SUBJECTS - Hasibuan, Ahmad Jubeir (Journal of Physical Education, Health and Sports Recreation, 2024)
The aim of this research is to determine the perceptions of SMAS PAB 8 Saentis students towards the independent learning curriculum in Physical Education, Sports and Health (PJOK) subjects. The method used in this research is a survey method. The population is because in this school only classes X and XI have actively implemented the Independent Learning Curriculum. The research sample was in class X with a sample size of 39 students and class XI with a sample size of 31 students. The instrument used in this research used a questionnaire, the variable in this research was the perception of SMAS PAB 8 Saentis students towards the Independent Learning Curriculum in Physical Education, Sports and Health (PJOK) subjects and the data analysis technique used was descriptive qualitative and quantitative. The results of the research show that the perception of SMAS PAB 8 Saentis students towards the independent learning curriculum in Physical Education, Sports and Health (PJOK) subjects has 2 class levels consisting of class X with a sample size of 39 students consisting of 6 classes with a percentage of 81% with the very good category and class XI with a sample size of 31 students consisting of 4 classes has a percentage of 83% in the very good category. Because of this, it can be concluded that the perception of SMAS PAB 8 Saentis students towards the independent learning curriculum in Physical Education, Sports and Health (PJOK) subjects has a very good category in accordance with what the researchers wanted.